WORDS PRODUCTION BASED ON MEMORY RECALL THROUGH NARRATIVE WRITING - audi yundayani (Journal of English Language and Literature (JELL), 2019)
Producing words refers to the mental process of retrieval of information that has been previously encoded and stored in the human brain. The aim of this research is to identify and describe words production based on memory recall through narrative writing. This research is a qualitative approach by using a descriptive qualitative method. Data and data sources are students’ narrative writing and strengthened by a semi-structured interview. The research finding shows that word production based on memory recall through narrative writing is influenced by some factors. They are 1) psychological factors, like motivation, 2) frequency of words using, 3) the understanding of the concept, and 4) schemata that is related to stored memory. These findings should be a guideline for the instructor to give a stimulus in developing students’ words production.